O estatuto lexical das preposições sob e sobre - Pezatti, Erotilde Goreti [UNESP]; Camacho, Roberto Gomes [UNESP] (My University, 2010)
This paper describes the prepositions sob and sobre in the Functional Discourse Grammar framework (HENGEVELD; MACKENZIE, 2008) aiming at checking their lexical or grammatical status on the basis of classification criteria postulated by Keizer (2007). The following aspects point to their lexical status : (i) they consist of an Ascription Subact; (ii) they contain a specific content on the vertical axis signaling inferiority and superiority position in relation to a limit; (iii) they are not required by any predicate, but they are predicates by themselves, which require complementation by an argument playing Reference semantic function; (iv) they may be combined with de, em, para and por; which are genuine grammatical prepositions; and, finally, (v) they are not subjected to any phonological process of reduction and fusion.

Este trabalho pretende descrever as preposições sob e sobre dentro do arcabouço da Gramática Discursivo-Funcional (HENGEVELD;MACKENZIE 2008), com o objetivo de verificar seu estatuto lexical ou gramatical no português, com base em critérios de classificação postulados por Keizer (2007). Os seguintes aspectos apontam para o estatuto lexical delas: (i) constituem um Subato de Atribuição; (ii) apresentam sentido específico, indicando, no eixo vertical, posição de inferioridade e superioridade em relação a um limite; (iii) não são exigidas por nenhum predicado, mas elas próprias exigem complementação, tendo seu argumento a função semântica Referência; (iv) podem combinar-se com de, em, para e por, que são verdadeiras preposições gramaticais; e (v) não se submetem a processos fonológicos de redução ou fusão.
The lexical status of the prepositions sob and sobre
Keywords: funcionalismo; preposição; categoria lexical; categoria gramatical; functionalism; preposition; grammatical category; lexical category